Experimental Results of a Wind Energy Conversion System with STATCOM Using Fuzzy Logic Controller - S. A. Gawish; S. M. Sharaf; MS El-Harony (Institute of Advanced Engineering and Science, 2016)
This paper describes a complete implementation of the experimental voltage regulation of a wind energy conversion system using STATCOM. Firstly conventional control technique is used which is proportional plus integral controller. The control technique is performed using a PC computer through a suitable interfacing and opt-isolating facilities. Secondly fuzzy logic controller is facilitated in this scheme to improve the performance of the experimental setup. Several efforts are done to choose the suitable gains of the fuzzy controller to achieve superior performance of the wind system. Experimental results of the system show the effectiveness of the proposed technique in regulating the output voltage. Thanks to the operation of the STATCOM in controlling the reactive power of the system to fix the output voltage at the desired value regardless of the wind speed.